The Influence of Digital-Based Differentiation Learning on Student's Well-Being Behavior (Current Research in Education: Conference Series Journal, 2024)
This research aims to investigate the effect of digital-based differentiated learning on students' welfare behavior. Student well-being is an important parameter in assessing educational success, and with the development of digital technology in education, it is important to understand its impact on student well-being. The research method used was an experimental study using two groups of students: an experimental group that received digital-based differentiation learning and a control group that received conventional learning. Data is collected through surveys and observations of student behavior over a certain period. Student welfare variables are assessed through indicators such as happiness level, learning motivation, sleep quality, stress level, and level of engagement in learning. The research results show that digital-based differentiated learning has a significant positive influence on student welfare. Students in the experimental group tended to be happier, more motivated, had better quality sleep, experienced lower levels of stress, and were more involved in the learning process compared to the control group. These findings show that the use of digital technology in learning can improve student well-being, which in turn can contribute to improving the quality of education. Therefore, digital-based differentiated learning needs to be considered in curriculum development and learning strategies in the future.